-3x-2(5y-7)=-12

Simple and best practice solution for -3x-2(5y-7)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-2(5y-7)=-12 equation:


Simplifying
-3x + -2(5y + -7) = -12

Reorder the terms:
-3x + -2(-7 + 5y) = -12
-3x + (-7 * -2 + 5y * -2) = -12
-3x + (14 + -10y) = -12

Reorder the terms:
14 + -3x + -10y = -12

Solving
14 + -3x + -10y = -12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -3x + -14 + -10y = -12 + -14

Reorder the terms:
14 + -14 + -3x + -10y = -12 + -14

Combine like terms: 14 + -14 = 0
0 + -3x + -10y = -12 + -14
-3x + -10y = -12 + -14

Combine like terms: -12 + -14 = -26
-3x + -10y = -26

Add '10y' to each side of the equation.
-3x + -10y + 10y = -26 + 10y

Combine like terms: -10y + 10y = 0
-3x + 0 = -26 + 10y
-3x = -26 + 10y

Divide each side by '-3'.
x = 8.666666667 + -3.333333333y

Simplifying
x = 8.666666667 + -3.333333333y

See similar equations:

| -5+3x=3(x-6)+13 | | 180(n-2)=156 | | t(n)=14-3(447) | | 6w=8w-40 | | 1.04x/3.14=7.98 | | 19u-17u-u=20 | | 3x^3-x*y=5 | | x+6=x-4 | | ln8/ln4 | | ln8/lnr4 | | ln8/lv4 | | 9m+10-4m=-5 | | (5/9)x^2-(16/5)x-3/2=0 | | 10s-6s-3s-1=13 | | 3(8-x)-5=-6x-4+3n | | 3x-10+2x=-65 | | t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= | | 5b-b-1=7 | | 2qt=c | | 8x+3y=37 | | 3(t)=67-16t^2 | | p(x)=5x^2-3x+2 | | t(n)=24-5(447) | | 19w-9w-9w+3=20 | | 8x=37-3y | | -3x+3=2x | | (3x+1)(1x+2)= | | 8n=15model | | Xy=126 | | 14n-13n=15 |

Equations solver categories